Prospective Study of Eye Disease in Timor-Leste: The East Timor Eye Program. Issue 5 (September 2016) - Sugnanam, Kirthi Kumar Naidu; Ma, Shirley; Kreis, Andreas; Correia, Marcelino; Verma, Nitin; Dirani, Mohamed
Abstract : Purpose: This study aimed to present the methodology of the East Timor Eye Program and report the prevalence of eye disease seen at the National Eye Centre during a 3-month sample period between June and August 2012. Design: Two hundred ninety-three new patients aged 17 years or older were assessed at the National Eye Centre in Dili, Timor-Leste. Methods: All participants received a comprehensive dilated eye examination that included distance visual acuity measurements, indirect fundoscopy, and a complete slit lamp assessment including gonioscopy and intraocular pressure measurement. Each patient completed an interview-administered general questionnaire, and information on general health, ocular history, and medication was obtained. Anthropometric measurements were also taken and recorded. Results: A total of 293 patients, 183 males (62.5%) and 110 females (37.5%), aged between 17 and 88 years (mean, 47.66 years) were recruited and examined. The 3 most common clinical eye presentations were conjunctival disorders (60.41%), followed by lens disorders (48.12%) and scleral, corneal, iris, and ciliary body disorders (46.42%). The 3 most common conditions causing blindness (visual acuity less than 3/60 as defined by the World Health Organization) were lens disorders (45.9%), choroidal and retinal disorders (18.9%), and other disorders of the eye and adnexa (13.5%). Conclusions: The East Timor Eye Program is an effective program that has enabled the management and treatment of various eye conditions in residents of Timor-Leste. The program set high standards for stringent and accurate data collection and ophthalmic diagnoses in a low-resource setting. Lens disorders and choroidal and retinal disorders were the most common conditions causing blindness.